Cytochrome c nitrite reductase from Desulfovibrio desulfuricans ATCC 27774. The relevance of the two calcium sites in the structure of the catalytic subunit (NrfA) - Cunha, Carlos A. (2019)
The gene encoding cytochrome c nitrite reductase (NrfA) from Desulfovibrio desulfuricans ATCC 27774 was sequenced and the crystal structure of the enzyme was determined to 2.3-Å resolution. In comparison with homologous structures, it presents structural differences mainly located at the regions surrounding the putative substrate inlet and product outlet, and includes a well defined second calcium site with octahedral geometry, coordinated to propionates of hemes 3 and 4, and caged by a loop non-existent in the previous structures. The highly negative electrostatic potential in the environment around hemes 3 and 4 suggests that the main role of this calcium ion may not be electrostatic but structural, namely in the stabilization of the conformation of the additional loop that cages it and influences the solvent accessibility of heme 4. The NrfA active site is similar to that of peroxidases with a nearby calcium site at the heme distal side nearly in the same location as occurs in the class II and class III peroxidases. This fact suggests that the calcium ion at the distal side of the active site in the NrfA enzymes may have a similar physiological role to that reported for the peroxidases.